OFR-17-80 Development Of Cross Pit Overburden And Waste Material Handling System (Phase II) - Russell J. Gartrell (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report describes the engineering feasibility and economic advantages of using a steep angle conveyance (SAC) system in conjunction with medium and large draglines to transport spoil in a typical Western Coal Mine. The SAC system, including a receiving hopper, a steep angle conveyor and a sticker/spreader, is capable of processing overburden material at the rate of 7,000 tons/hr. The unique feature of this system is the steep angle conveyor which transports the overburden material from the pit bottom to the top of the spoil at angles to 45 degrees. Compared to other means of cross-pit conveyance considered during this study, the SAC system offers the advantage of easier operation, lower conveyance cost and greater mobility. The results of this study have shown that integration of the SAC system into both established and planned new mines would improve the overall mining operation, expand the operating capability of existing equipment and reduce mining end reclamation cost.